Perancangan Pembangkit Listrik Tenaga Angin Dengan Turbin Ventilator Sebagai Penggerak Generator - Padmika, Made; Satriya Wibawa, I Made; Trisnawati, Ni Luh Putu (BULETIN FISIKA; Vol 18 No 2 (2017): BULETIN FISIKA, 2017)
A prototype of a wind power plant had been created using a ventilator  as a generator spiner. This power plant utilizes wind speed as its propulsion. Electricity generated in the DC voltage form between 0 volts up to 7.46 volts. The MT3608 module is used to stabilize and raise the voltage installed in the input and output of the charging circuit. For instrument testing, the wind speed on 0 m/s up to 6 m/s interval used. Maximum output of this tool with a wind speed of 6 m/s is 7.46 volts.